Retinoic acid-inducible gene-I like receptor pathway in cancer: modification and treatment - Du, Guangyuan; Xing, Zherui; Zhou, Jue; Cui, Can; Liu, Chenyuan; Liu, Yiping; Li, Zheng (Frontiers in Immunology, 2023)
Retinoic acid-inducible gene-I (RIG-I) like receptor (RLR) pathway is one of the most significant pathways supervising aberrant RNA in cells. In predominant conditions, the RLR pathway initiates anti-infection function via activating inflammatory effects, while recently it is discovered to be involved in cancer development as well, acting as a virus-mimicry responder. On one hand, the product IFNs induces tumor elimination.On the other hand, the NF-κB pathway is activated which may lead to tumor progression. Emerging evidence demonstrates that a wide range of modifications are involved in regulating RLR pathways in cancer, which either boost tumor suppression effect or prompt tumor development. This review summarized current epigenetic modulations including DNA methylation, histone modification, and ncRNA interference, as well as post-transcriptional modification like m6A and A-to-I editing of the upstream ligand dsRNA in cancer cells. The post-translational modulations like phosphorylation and ubiquitylation of the pathway's key components were also discussed. Ultimately, we provided an overview of the current therapeutic strategies targeting the RLR pathway in cancers.